Tobacco: A Brief Report and Recent Trends in Indian Scenario - Dutta Malik, Shilpa; Malik, Upender; Ravi, Jyoti (International Journal Of Drug Research And Dental Science, 2022)
This paper comprehensively encloses the various aspects of tobacco cessation along with its prevalence in particular reference to the Indian scenario., Genotoxicity associated with tobacco, and its effects on oral & systemic health. Tobacco a manmade pandemic is a leading cause of death, killing nearly six million people worldwide each year. India is the second-largest consumer of tobacco globally, and accounts for approximately one-sixth of the world’s tobacco-related deaths. The tobacco problem in India is untypical with the consumption of a variety of smokeless and smoking forms. To understand the tobacco problem in India. it’s mandatory to understand the disparate prevalence of tobacco use at various geographical locations. For effective tobacco cessation, users should be made aware of the life-threatening effects of tobacco.